Influence of dietary carnitine and/or chromium on blood parameters of gestating sows - Woodworth, J.C.; Tokach, Michael D.; Koo, S.I.; Minton, J. Ernest; Owen, K.Q.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Gestating sows (n=44; parity=2.0; BW=458 lb) were used to determine the effects of dietary Carnitine and/or chromium picolinate on daily blood parameter profiles. Diets were formulated as a 2 × 2 factorial with carnitine (0 or 50 ppm) and chromium (0 or 200 ppb) and were fed from breeding, through gestation, lactation, and 30 d into the next gestation at which time blood was collected. Sows were fed one meal per day during gestation (2.1 kg) and ad libitum during lactation. Sows were fitted with indwelling venous catheters and blood (plasma) was collected at feeding, once every 15 min for the first 3 h after feeding, and at 6, 9, 15, 20, and 24 h after feeding. Chromium picolinate elicited its greatest effect immediately after feeding (0-3 h) by decreasing (P<0.05) insulin and cpeptide, whereas Carnitine decreased (P<0.05) NEFA and urea N (PUN) in the fasting state (6-24 h post-feeding). Sows fed both carnitine and chromium exhibited intermediate responses. Post-feeding glucose peak was lower (P<0.05) for diets with carnitine and/or chromium versus the control and mean glucose concentration was lower (P<0.01) for sows fed diets with chromium. Mean insulin and cpeptide concentration was lowest (P<0.01) for sows fed the diet with chromium and highest for sows fed the control, with sows fed diets with carnitine or carnitine and chromium having intermediate responses (Carnitine × chromium, P<0.01). Mean NEFA was lower (P<0.01) for sows fed diets with carnitine. Mean NEFA and glycerol were higher (P<0.03) for sows fed the diets with chromium. Sows fed the diet with only carnitine had the lowest PUN, but no differences were observed between the other three diets (carnitine × chromium, P<0.01). Dietary carnitine increased (P<0.05) the circulating leptin concentration, specifically in the fasting portion of the day. Both carnitine and chromium were observed to influence (P<0.05) the concentrations of some amino acids. No differences were observed for IGF-1, IGFBP-3, glucagon, or triglyceride (P>0.10); however, sows fed carnitine had numerically higher (P=0.11) IGF-1 and IGFBP-3 (P=0.06). In summary, the changes in metabolites and metabolic hormones indicate that both carnitine and chromium influence energy metabolism of gestating sows; however, their effects on blood parameters are different. Thus, the improvement in energy status from adding both carnitine and chromium may have an additive effect on reproductive performance of sows.
Keywords: Sows; Carnitine; Chromium; Blood Parameters; Swine